Preparation and Characterization of Poly(Methyl Methacrylate) Grafted Sago Starch - Qudsieh, Isam Yassin Mahmood (1999)
The graft copolymerization of poly(methyl methacrylate) (PMMA) onto sago starch (sago starch-g-PMMA) was carried out using ceric ammonium nitrate (CAN) and potassium persulfate (PPS) as initiators. PMMA was first grafted onto sago starch using CAN as an initiator under nitrogen gas atmosphere. The maximum percentage of grafting (%G) was detennined to be 2460/0 when the optimum conditions (reaction temperature: 70 DC, reaction period: 2 hrs, the amount of CAN: 2.0 mmoles, the amount of nitric acid: 0.4 mmoles, and the amount of methyl methacrylate (MMA): 141 mmoles). When PPS was used as an initiator, the maximum % G achieved was 900/0. The optimum conditions for this initiator were as follows: reaction temperature: 50 oC, the amount of monomer: 47 mmoles, the amount of PPS: 1.82 mmoles, and reaction period: 1.5 hr. The copolymers produced were characterized by Fourier Transform Infrared Spectrophotometry (FTIR) , differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). The FTIR spectra of the copolymers clearly indicated the presence of characteristic peaks of PMMA and sago starch, which suggested that PMMA had been successfully grafted on the sago starch. DSC and TGA thermograrns showed that the copolymerization products were made up of two different polymers. The copolymers of vanous percentages of grafting were hydrolysed with 0.5 M hydrochloric acid and the viscosity measurements of PMMA produced were carried out using Ubbelohde viscometer. The average molecular weight (Mv) of PMMA grafted onto the sago starch (2460/0G) prepared by using CAN as the initiator was 4.3xlO4, and from PMMA grafted sago starch (900/00) prepared by using PPS as the initiator was 1.3x 104. Biodegradability studies of sago starch-g-PMMA and sago starch were carried out by a-amylase enzyme. The rate of degradation of sago starch was higher than the rate of degradation of sago starchg- PMMA. Maximum biodegradation of the sago starch was achieved after 3 days of incubation, while for the copolymer was 7 days.